Edukasi Tentang Pengelolaan dan Pengembangan Usaha Kecil Menengah (UKM) Bagi Pedagang Kaki Lima di Jagakarsa Jakarta Timur - aditya, aditya aditya; Septian, Hudan (SYUKUR (Jurnal Inovasi Sosial dan Pengabdian Masyarakat), 2018)
Dedication activites to the community as to missionary endeavoe has purpose to improving themselves to undergo all activities in the month of Ramadan, introduce, instill, and growing a sense of concern for others. Methods in the implementation of community service programs are initial observation of activity areas, mapping of problems, socialization of activities, and looking for fund. Output of community service activities is to helping community around Jagakarsa district, increasing the involvement and reach of universities especially students in community service programs and increasing caring for others.